(untitled) (LACCEI, 2024)
This project proposes an automatic system in Lomas de Paraíso, which allows tara plantations to be irrigated automatically and manually throughout their vegetative process. This technified irrigation system can be operated both locally with a panel that has a human-machine interaction interface, and remotely through a mobile application. It also presents scalability allowing to increase irrigation zones and to be able to be replicated in other places due to its low cost and easy operation.